Aves da Chapada dos Guimarães, Mato Grosso, Brasil: uma síntese histórica do conhecimento - Lopes, Leonardo Esteves; Pinho, João Batista de; Bernardon, Bianca; Oliveira, Fabiano Ficagna de; Bernardon, Giuliano; Ferreira, Luciana Pinheiro; Vasconcelos, Marcelo Ferreira de; Maldonado-Coelho, Marcos; Nóbrega, Paula Fernanda Albonette de; Rubio, Tatiana Colombo (Papéis Avulsos de Zoologia, 2009)
Here we present a historical review of all known ornithological surveys carried out at Chapada dos Guimarães, central-western Brazil. We characterize the avifauna of the region following a critical review of all bird species listed by several generations of ornithologists. The final species account was produced based on extensive literature and museum consultation and on recent field work. Special attention is given to the series of papers by J.A. Allen, which was based on the monumental collecting work by H.H. Smith and his wife on the 19th century. The study area is predominantly characterized by a Cerrado bird assemblage and in a lesser extent, by Amazonian elements. A total of 393 bird species have confident records for the region. Other 52 species were cited for the region, but were judged unlikely to occur in the study area under our stringent criteria. Twenty four species collected by the Smiths are no longer recorded in the region. Six of these species are sensitive grassland specialists, and three are popular cagebirds. These species are probably extinct in the area. Seven species are waterbirds and two are Amazonian species, all of them have probably always been very rare in the region due to the lack of apropriate habitat. Six species are naturally rare, and could be overlooked. We report the first documented record of Caprimulgus longirostris for Mato Grosso and the second record of Pipraeidea melanonota for the state. We also comment on several apparently rare species on the region such as Ictinia mississipensis, Buteo melanoleucus, Harpia harpyja, Megascops usta, Asio flammeus, Berlepschia rikeri, Euscarthmus rufomarginatus, Xenopsaris albinucha, and Poospiza cinerea.